Bone Turnover Markers and Probable Advanced Nonalcoholic Fatty Liver Disease in Middle-Aged and Elderly Men and Postmenopausal Women With Type 2 Diabetes - Wang, Ningjian; Wang, Yuying; Chen, Xiaoman; Zhang, Wen; Chen, Yi; Xia, Fangzhen; Wan, Heng; Li, Qing; Jiang, Boren; Hu, Bin; Lu, Yingli (Frontiers in Endocrinology, 2020)
Objective: Type 2 diabetic patients have a higher incidence of nonalcoholic steatohepatitis (NASH) and advanced stages of fibrosis, and nonalcoholic fatty liver disease (NAFLD) is associated with impaired bone health. We aimed to investigate whether bone turnover is associated with the probable presence of NASH and fibrosis. Methods: In total, 4,937 diabetic participants from Shanghai, China were enrolled in 2018. Subjects with NAFLD were categorized into simple NAFLD and probable NASH groups based on the presence of metabolic syndrome. The NAFLD fibrosis score was used to identify patients with a higher likelihood of advanced fibrosis. Results: In postmenopausal women, large N-mid fragment of osteocalcin (N-MID osteocalcin) was negatively associated with probable NASH (P for trend < 0.001). β C-terminal cross-linked telopeptides of type I collagen (β-CTX) and procollagen type I N-terminal propeptide (P1NP) were positively associated with the probable presence of significant fibrosis in postmenopausal women (P for trend 0.015 and < 0.001). However, in men, N-MID osteocalcin and β-CTX were negatively associated with the probable presence of significant fibrosis (P for trend 0.029 and 0.027). Conclusions: Significant associations among N-MID osteocalcin, β-CTX and P1NP and probable advanced NAFLD were observed. Further prospective and animal studies are warranted to understand the causal relationship and underlying mechanism.